Children’s Nutrition Status and Motor Development in Middle Class Parents Social Economy Status (SES) - Stephani, Mesa Rahmi; Suherman, Adang; Syihab, Syifa; Putri, Wulandari; Sumarno, Gano; Wibowo, Ricky (TEGAR: Journal of Teaching Physical Education in Elementary School, 2021)
The development of early childhood needs to be considered, considering the child is a parent investment in the future. Meeting the nutritional needs of children has an important role in achieving optimal growth and development, and is one of the determinants of achieving these needs. Nutritional status in children in the school environment often uses height and weight parameters. This study aims to determine the effect of nutritional status on early childhood on motor skills. The method used is ex-post facto in the sample of early childhood aged four to five years who have attended kindergarten with middle-level socioeconomic status. Nutritional status is known through height and weight, gross and fine motor development measured using ASQ 3rd edition. Data was processed with SPSS using the Kruskal Wallis Test analysis technique. The results show 90% of children are in the Thin category, 6.7% are in the Normal category, and 3.3% are in the obesity category. There is no influence of nutritional status on gross and fine motoric abilities in kindergarten children. The results of this study can be used as a consideration for the government to pay attention to nutritional status and motoric abilities of children, in an effort to minimize the gap between the quality of education and the various backgrounds of parents' socio-economic status.